Detection of EML4-ALK Fusion Gene in Chinese Non–Small Cell Lung Cancer by Using a Sensitive Quantitative Real-Time Reverse Transcriptase PCR Technique. Issue 4 (April 2015) - Fu, Sha; Wang, Fang; Shao, Qiong; Zhang, Xu; Duan, Li-Ping; Zhang, Xiao; Zhang, Li; Shao, Jian-Yong
Abstract : Anaplastic lymphoma kinase (ALK) rearrangement is present in approximately 5% of lung adenocarcinoma. Clinical trials on ALK inhibitor phase I to III have shown an interesting disease control rate and acceptable tolerability in ALK rearrangement patients. In clinical application, the precise diagnostic strategy for identifying ALK rearrangements remains to be determined. In this study, ALK rearrangement was screened by using quantitative real-time reverse transcriptase polymerase chain reaction (qRT-PCR), direct sequencing, 2 fluorescence in situ hybridization (FISH) assays, and immunohistochemistry in 173 lung adenocarcinomas. We identified 18 cases (10.4%) with EML4-ALK fusion-positive by qRT-PCR, and all were positive for EML4-ALK fusion gene validated by direct sequencing. The result was consistent with that of other methods. Furthermore, of the 18 EML4-ALK fusion-positive cases, 16 (9.2%) were positive by using EML4-ALK fusion probe FISH, and 15 (8.7%) were positive by using ALK break-apart probe FISH and immunohistochemistry staining. Of the 18 ALK fusion-positive lung adenocarcinomas, 8 cases (44.4%) were histologically diagnosed as subtypes of cribriform adenocarcinoma, 7 cases (38.9%) as cribriform adenocarcinoma mixed with papillary and/or mucinous pattern, 2 cases (11.1%) as papillary adenocarcinoma, and 1 case (5.6%) as mucinous adenocarcinoma. In the present study, the ALK rearrangement frequency detected by qRT-PCR in Chinese NSCLC patients was higher than that in the western populations. QRT-PCR is a rapid, sensitive technology that could be used as a screening tool for identifying EML4-ALK fusion-positive NSCLC patients who would be sensitive for receiving ALK inhibitor therapy. Abstract : Supplemental Digital Content is available in the text.